2020
DOI: 10.3390/en13040818
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and Modeling for Flexible Biogas Production by Co-Digestion of Food Waste and Sewage Sludge

Abstract: This paper explores the feasibility of flexible biogas production by co-digestion of food waste and sewage sludge based on experiments and mathematical modeling. First, laboratory-scale experiments were carried out in variable operating conditions in terms of organic loading rate and feeding frequency to the digester. It is demonstrated that biogas production can achieve rapid responses to arbitrary feedings through co-digestion, and the stability of the anaerobic digestion process is not affected by the overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…which are achievable theoretically and also it is used to determine the different process parameters. The biogas obtained from dry AD of food waste with pretreatment in two different phased (pretreatment of food waste at 0.5-,1-, 1.5-, 2-, 2.5-kg/cm 2 pressure and pretreatment of food waste at 120 • C and 2-kg/cm 2 pressure for 20, 40, 60, 80 and 100 min) experiments was mathematically modeled by using modified Gompertz equation, which has been established as empirical nonlinear regression model and it is developed by Zwietering [31] in order to determine the kinetics of specific growth rate of methanogenic bacteria in the reactor for the biogas production. The Gompertz equation is basically used in sigmoidal growth curves [32,33] and the equation of modified Gompertz model is described in the Equation (2).…”
Section: Kinetic Model For Biogas Generationmentioning
confidence: 99%
“…which are achievable theoretically and also it is used to determine the different process parameters. The biogas obtained from dry AD of food waste with pretreatment in two different phased (pretreatment of food waste at 0.5-,1-, 1.5-, 2-, 2.5-kg/cm 2 pressure and pretreatment of food waste at 120 • C and 2-kg/cm 2 pressure for 20, 40, 60, 80 and 100 min) experiments was mathematically modeled by using modified Gompertz equation, which has been established as empirical nonlinear regression model and it is developed by Zwietering [31] in order to determine the kinetics of specific growth rate of methanogenic bacteria in the reactor for the biogas production. The Gompertz equation is basically used in sigmoidal growth curves [32,33] and the equation of modified Gompertz model is described in the Equation (2).…”
Section: Kinetic Model For Biogas Generationmentioning
confidence: 99%
“…Thus, the actions aimed at implementing the low-energy or passive WWTPs are being taken [20]. These result in a reduction of the operational costs, improvement of stability and reliability of the wastewater treatment processes, as well as mitigation of the WWTP impact on the aquatic environment [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Co-digestion with sewage sludge is a valid way for the AD of food waste, since sewage sludge is able to provide the alkalinity and micronutrients required for the AD reaction ( Nghiem et al, 2017 ). Some researchers have already shown that if the co-digestion of food waste and sludge is implemented, abrupt increments of the feeding OLR can be adopted without negative impacts on the AD reaction process performance ( Liu et al, 2020 ). On the other hand, the key for implementation of the DO is a valid biogas production process control system ( Mauky et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main mathematical equations for predicting biogas production under the flexible operating mode (seen in Equations (4) and ( 5 )) are based on the modified first-order kinetics model. For detailed explanations of this equation, refer to Liu et al (2020) …”
Section: Modelling Methodsmentioning
confidence: 99%
See 1 more Smart Citation